Diario de Santa María, a heterogeneity novel - Vargas Bautista, Abraham (2023)
This article analyzes the novel Diario de Santa María by Edgardo Rivera Martínez. Critics have agreed to highlight the harmonic miscegenation as the great contribution of his work. This concept refers to the representation of a horizontal relationship between Andean and Western cultures. So, the novel would be proposing a society without social conflicts, where the portrayed societies manage to coexist peacefully and symmetrically. The analysis proposed in this article is a critique of the idea of harmonic miscegenation. Our reading is based on the category of heterogeneity of Cornejo Polar. This concept has allowed us to take a critical look at the harmonic miscegenation in Diario de Santa María. We conclude that although racism and classism do not govern the interpersonal relationships between the characters, a colonial thought does underlie the work, where European culture enjoys greater prestige in the imaginary of the main character.